The importance of nurses hand hygiene - Malliarou, Maria; Zyga, Sofia; Constantinidis, Theodoros C.; Sarafis, Pavlos (My University, 2013)
Introduction: Nurses are aware of the rationale for hand hygiene procedures. Nurses represent a large working group that performs the greatest amount of direct patient care in Health Services. Hand hygiene is one of the most effective measures to prevent hospital acquired infections. Aim: to point out the importance of nurses’ hand hygiene Method: a review of articles with key words “hand, hygiene, hand, contamination, nurse, and guideline”. Results: Infectious diseases are a particular risk to the very young, the elderly, those with a preexisting disease, and people with a compromised immune system. Nurses washing their hands not only prevent them from getting sick, but it also reduces the risk of infecting others.
Keywords: Hand hygiene; Hand contamination; Health care-associated infection